High-resolution ∼55 ka paleomagnetic record of Biển Hồ maar lake sediment from Vietnam in relation to detailed 14C and 137Cs geochronologies - Ojala, Antti; Nguyễn-Văn, Hướng; Unkel, Ingmar; Nguyễn-Thùy, Dương; Nguyễn-Đình, Thái; Đỗ-Trọng, Quốc; Sun, Chunqing; Sauer, Peter E.; Schimmelmann, Arndt (Quaternary geochronology, 2023)
Vietnam's Central Highlands in Pleiku feature numerous volcanic craters (i.e. maars) formed over 0.2 Ma ago that contain continuous high-resolution lacustrine sediment records extending from the Late Pleistocene through the Holocene. Their evolution and sedimentary proxies are potentially powerful archives for interpretation of East-Asian monsoon variability across Vietnam, as well as for local to regional changes in landcover. The focus of this study is to develop a reliable chronology for the Biển Hồ 25-m-long lake sediment sequence in Vietnam's Central Highlands. We present a combined sediment chronology extending back to 55 ka cal BP that is based on 137Cs surface sediment chronology, paleomagnetic dating, and 47 14C dates distributed evenly throughout the sequence. Based on sedimentary facies analysis and a smooth age-depth model based on 137Cs and 14C data, we infer a long-term stable rate of sedimentation in Biển Hồ lake without unconformities or erosional hiatuses, except for the uppermost section (ca. 100 years) where human activities increase the rate of sedimentation significantly. The Biển Hồ sequence thus provides a complete and uninterrupted record of the lake's depositional history. The present contribution is a geochronologic opening salvo for future contributions from Biển Hồ lake featuring multi-disciplinary evidence for longer-term paleoclimate and environmental changes.